Are we following the guidelines on non-muscle invasive bladder cancer? - Reis, Leonardo Oliveira (2016)
Objectives: To evaluate the clinical practice of non-muscle invasive bladder cancer (NMIBC) treatment in Brazil in relation to international guidelines: Sociedade Brasileira de Urologia (SBU), European Association of Urology (EAU) and American Urological Association (AUA). Materials and Methods: Cross-sectional study using questionnaires about urological practice on treatment of NMIBC during the 32nd Brazilian Congress of Urology. A total of 650 question forms were answered. Results: There were 73% of complete answers (total of 476 question forms). In total, 246 urologists (51.68%) lived in the southeast region and 310 (65.13%) treat 1 to 3 cases of NMIBC per month. Low risk cancer: Only 35 urologists (7.5%) apply the single intravesical dose of immediate chemotherapy with Mitomicin C recommended by the above guidelines. Adjuvant therapy with BCG 2 to 4 weeks after TUR is used by 167 participants (35.1%) and 271 urologists (56.9%) use only TUR. High risk tumors: 397 urologists (83.4%) use adjuvant therapy, 375 (78.8%) use BCG 2 to 4 weeks after TUR, of which 306 (64.3%) referred the use for at least one year. Intravesical chemotherapy with Mitomicin C (a controversial recommendation) was used by 22 urologists (4.6%). BCG dose raised a lot of discrepancies. Induction doses of 40, 80 and 120mg were referred by 105 (22%), 193 (40.4%) and 54 (11.3%) respectively. Maintenance doses of 40, 80 and 120mg were referred by 190 (48.7%), 144 (37.0%) and 32 (8.2%) urologists, respectively. Schemes of administration were also varied and the one cited by SWOG protocol was the most used: 142 (29.8%). Conclusion: SBU, EAU and AUA guidelines are partially respected by Brazilian urologists, particularly in low risk tumors. In high risk tumors, concordance rates are comparable to international data. Further studies are necessary to fully understand the reasons of such disagreement.